Composition, dielectric breakdown, and bandgap of ultra-thin amorphous boron oxynitride produced by magnetron sputtering. (June 2021) - Arnold, Corey L.; Iheomamere, Chukwudi E.; Dockins, Maddox; Gellerup, Spencer; Glavin, Nicholas R.; Muratore, Christopher; Shepherd, Nigel D.; Voevodin, Andrey A.
Abstract: Ultra-thin amorphous boron oxynitride films were deposited at room temperature on silicon and polymer substrates using radio frequency magnetron sputtering of a hexagonal boron nitride target in varied argon-nitrogen background gas ratios. The effects of nitrogen content in the sputtering gas, changes in target-to-substrate distance, and magnetron power density on the film composition were investigated with X-ray photoelectron spectroscopy and correlated to the dielectric breakdown strength and bandgap obtained from current-voltage measurements and Tauc plots. Films grown in pure Ar atmosphere at a large target-to-substrate distance displayed compositions containing metallic boron, which led to a decrease in the dielectric breakdown strength. The use of Ar:N2 mixtures and pure N2 eliminated metallic boron bonding. Decreasing the target-to-substrate distance and target power density during reactive sputtering resulted in B:N stoichiometry ratio closer to one and about 25–30 at.% oxygen. Smooth surface morphology films grown in pure N2 at a small target-to-substrate distance exhibited dielectric breakdown strength of 2.1–2.4 MV cm −1 at 30 nm film thickness and bandgap of 5.4 eV. The results show the suitability of amorphous boron oxynitride for application as an insulator or gate dielectric in thin-films flexible transistors and other electronics when a low processing temperature is required. Highlights: Ultra-thin pinhole-free amorphous boron oxynitride (a-BON) films produced at room temperature by reactive RF sputtering. Growth conditions optimized to eliminate metallic boron bonding in a-BON films on silicon and polymer substrates. Large band-gap measured for a-BON films with about 1:1 ratio of boron and nitrogen and 25–30 at.% oxygen. Dielectric breakdown strength of 30 nm thick a-BON films is comparable to high temperature grown boron nitride films.